EVALUATION OF DIFFERENT BRASSICA SPECIES AND ONION FOR THEIR BIOFUMIGATION EFFECT AGAINST Rhizoctonia solani f. sp. sasakii in vitro - G. BINDU MADHAVI, G. UMA DEVI , K. VIJAY KRISHNA KUMAR , T. RAMESH BABU; T.C.M. NAIDU (The Journal of Research ANGRAU, 2015)
Glucosinolate-containing Brassica spp. is known to release volatilic isothiocyanates (ITCs) which are toxic to different pathogens. The chemistry involved in the biofumigation can be attributed to the action of myrosinases on the glucosinolates (GLS) thereby releasing ITCs, thiocyanates, nitriles, oxalidine, dimethyl sulphide, methanethiol among other compounds.The present study was taken up to evaluate different Brassica spp and onion for their biofumigation effect against Rhizoctonia solani f. sp. sasakii in vitro. Among different brassica species, macerated mustard plant parts are effective in inhibition of radial growth and sclerotial production of Rhizoctonia solani f. sp sasakii. In all tested concentrations there was a positive association between increase of volumes and the rate of radial growth suppression.